The Influence of the Mudharabah Deposit Profit-Sharing System on Customer Interest in Investing in Sharia Banks - Wulandari, Weni; Sisilia, Ince (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Sharia institutions in Indonesia have experienced rapid growth over time, especially Sharia Banks. Currently, Indonesia is the fourth country that has great potential for the development of Sharia financial institutions. The difference in principles and systems is one of the reasons that make people interested in investing in Sharia Institutions, especially deposit investments that use the mudharabah system in calculating profits. In 2009, after carrying out a spin-off, PT Bank BNI Syariah succeeded in developing its business by adding more branches and increasing the number of third-party deposits. This research aims to find out the Mudharabah savings system, and how customers are interested in investing in Sharia Banks. And to find out the influence of the system that makes people interested in savings products. The location of this research is PT Bank BNI Syariah Bogor Branch one of the Sharia Banks that is of interest to the public. This research uses a descriptive method to determine and show the relationship between the mudharabah profit-sharing system and customer interest in investing. The research results show that the profit calculation system used by PT Bank BNI Syariah is profit sharing, with the savings contract used being Mudharabah Mutlaqah. Based on a review of PT BNI Syariah's annual report for 2010 – 2012, the number of DPK has increased. This is because PT Bank BNI Syariah products are trusted by customers. Apart from that, consumer knowledge about the Islamic Economy which uses a profit-sharing system is getting better. So it can be concluded that the profit-sharing system on mudharabah deposits can influence customers' interest in investing in deposits.